Factors influencing the outcome of acute lateral humeral condylar fracture in children and its related complications - Syafrein Effendi, Warith Muhammad (2015)
Back ground: Lateral condylar of humerus fractures are among the commonest fracture in children. Open reduction and internal fixation (ORIF) is the preferred option as it prevents complications caused by inaccurate reduction, however the outcomes remain variable. The purpose of this study is to determine factors influencing the overall functional outcome following lateral condylar fractures of humerus in children and to describe the complications that arise. Methods: There were children until the age of 14 years old for the girls and 16 years old for the boys were involved in this study. All of them were treated for lateral condyle humeral fracture for at least 1 year. They were selected and contacted after reviewing their radiological andtreatment records and were asked to come to HUSM for further evaluation. During evaluation, the functional ability of the involved elbow was assessed. A radiological assessment of affected limb was also performed through a proper antero-posterior radiograph. The functional outcome was assessed based on activity of daily living, range of motion and carrying angle of the affected elbow with the normal elbow and graded using Dhillon scoring system into excellent, good, fair and poor outcome. The amounts of residual displacement after treatment were documented. Data were statistically analysed using SPSS version 20. Result: Twenty-seven male and six female patients were involved in this study. The age at time of fracture was within 2 to12 years old with the mean of 6.3 years old. Thirteen patients had medial residual displacement between 3mm to 5mm and 20 patients had 2mm or less medial residual displacement. A large numbers of patients attained good functional outcome scoring (42.4%) followed by excellent score (27.3%). This is followed by fair score (24.2%). Only a small numbers of patient had poor scoring system (6.1%). Both residual medial intraarticular displacement and residual lateral cortex displacement post fracture treatment (both <2mm and 3mm-5mm) did not significantly affect the early functional outcome (Dhillon score) .( Multiple logistic regression, β = -0.19; 95% CI=-1.09, 0.40; p-value= 0.034) (Multiple logistic regression, β= -0.12,CI= -0.67,0.63, p-value 0.94). Age of fracture, type of treatment and method of surgical fixation are not statistically correlated with Dhillon score. In term of complications, only one patient (3.0%) had persistent pain, 14 (42.4%) patients clinically had lateral condyle prominence, 4 (12%),with cubitus varus deformity, 2 (6.1%) had fishtail deformity, 19 (57.6%) had osteophytes and there was no incidence of AVN and non union. All of these complications are not statistically associated with Dhillon scoring. Conclusion: This study shows that children who sustained lateral condyle of humerus fracture have excellent-good outcome (69.7%) after at least 1 year of follow up. The amount of medial and lateral residual displacement of lateral humeral condyle fracture did not affect the early functional outcome as long as it is within 5mm. The most common complications encountered are osteophytes (57.6%) and lateral condyle overgrowth (42.4%).